Prevalence and Associated Factors of Early Postnatal Care Service Use Among Mothers Who Had Given Birth Within the Last 12 Months in Adigrat Town, Tigray, Northern Ethiopia, 2018 - Gebreslassie Gebrehiwot T; Mekonen HH; Hailu Gebru T; Kiros KG; Gebresilassie B; Teklu G; Tesfay Tadese H; Haileslassie Y (Dove Medical Press, 2020)
Tesfay Gebreslassie Gebrehiwot,1 Haftea Hagos Mekonen,1 Tsegu Hailu Gebru,1 Kbrom Gmechu Kiros,1 Berhanu Gebresilassie,2 Guesh Teklu,1 Haileslassie Tesfay Tadese,1 Yared Haileslassie1 1Nursing Department, College of Medicine and Health Science, Adigrat University, Adigrat, Ethiopia; 2Midwifery Department, College of Medicine and Health Science, Adigrat University, Adigrat, EthiopiaCorrespondence: Tesfay Gebreslassie Gebrehiwot Tel +251-945-807-481Email gtesfisha@gmail.comBackground: The care given for the first hours, days, and weeks after childbirth is life-threatening. So far, this period receives less attention from health-care providers than the care given to pregnancy and delivery. This study aimed to determine the prevalence and associated factors of early postnatal care service use among mothers who had given birth in the last 12 months in Adigrat Town, Tigray, Ethiopia.Methods: A community-based cross-sectional study was conducted from March to April 2018 among 481mothers who had given birth in the last 12 months. A systematic random sampling technique was used to select study participants. A pre-tested and structured questionnaire was used to collect the data. Data analysis was computed using SPSS version 20. An adjusted odds ratio with a 95% confidence interval and p-value less than 0.05 was used to determine the level of significance.Results: The proportion of early postnatal care service utilization was 34.3% (95% CI: 29.9%– 38.5%). Mothers’ use of early postnatal care service was predicted by previous early postnatal care use (AOR=2.60, 95% CI: 1.41– 4.77), ANC visit (AOR=0.122, 95% CI:0.059– 0.251), delivery complication (AOR=5.57, 95% CI: 2.85– 10.89), distance (AOR =5.05, 95% CI: 2.45– 10.42), postnatal home visit (AOR=0.21, 95% CI: 0.11– 0.40), awareness on early postnatal care (AOR=16.38 95% CI: 6.23– 43.07), age (AOR=9.34, 95% CI: 1.73– 50.27), (AOR=6.50, 95% CI: 2.29– 18.41), (AOR= 6.23, 95% CI: 2.38– 16.33) and income (AOR=7.97 95% CI: 2.42– 26.26, AOR=3.30 95% CI:1.42– 7.67).Conclusion: Our study’s finding revealed that the prevalence of early postnatal care service use was low. Early postnatal care service use was significantly associated with previous early postnatal care use, delivery complication, distance, postnatal home visit, number of ANC visits, awareness on early postnatal care use, age, and income.Keywords: early postnatal care, factors, mothers, Adigrat, Ethiopia